2018
DOI: 10.1128/msphere.00506-18
|View full text |Cite
|
Sign up to set email alerts
|

Hog1 Regulates Stress Tolerance and Virulence in the Emerging Fungal Pathogen Candida auris

Abstract: The rapid global emergence and resistance of Candida auris to current antifungal drugs highlight the importance of understanding the virulence traits exploited by this human fungal pathogen to cause disease. Here, we characterize the stress resistance profile of C. auris and the role of the Hog1 stress-activated protein kinase (SAPK) in stress resistance and virulence. Our findings that C. auris is acutely sensitive to certain stresses may facilitate control measures to prevent persistent colonization in hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 61 publications
3
87
0
1
Order By: Relevance
“…However, studies by Day and colleagues characterized the responses of Candida to a variety of stresses, including high salinity, and showed that C. auris exhibited a unique stress resistance profile compared to those of other Candida spp. (22). Despite the different profiles, these responses involved the evolutionarily conserved Hog1 stress-activated protein kinase (SAPK).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies by Day and colleagues characterized the responses of Candida to a variety of stresses, including high salinity, and showed that C. auris exhibited a unique stress resistance profile compared to those of other Candida spp. (22). Despite the different profiles, these responses involved the evolutionarily conserved Hog1 stress-activated protein kinase (SAPK).…”
Section: Discussionmentioning
confidence: 99%
“…Additional indirect support for the role of cell morphology and structure in the different, clade-specific C. auris phenotypes described here comes from recent studies involving deletion of the evolutionarily conserved stress-activated protein kinase Hog1. Perturbation of the hog1 gene in C. auris isolates induced the formation of large cellular aggregates/clumps; increased resistance to cell wall-damaging agents, including the echinocandins; an increased exposure of chitin on the cell surface; and notably, a significant reduction in virulence in vivo (46). Further studies will be required to evaluate whether C. auris isolates from the different clades exhibit differences in Hog1 activity or activation profiles or differential interactions between Hog1 and associated mitogen-activated protein kinase pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has demonstrated that the stress-activated protein kinase Hog1 plays an evolutionarily conserved role in C. auris stress resistance, cell wall homeostasis, and virulence (Day et al, 2018). C. auris Hog1 shares 87% identity with the C. albicans Hog1 sequence.…”
Section: Stress Resistance and Persistencementioning
confidence: 99%